Stylometry and Automatic Attribution of Medieval Liturgical Monodies - Francesco Unguendoli; Giampaolo Cristadoro; Marco Beghelli (IJCoL)
While automatic attribution of literary text as well as stylometry evaluation are nowadays well-established research areas, much less has been done in the field of musicology. Here we present the results of the implementation of an automatic stylometric attribution technique to a corpus of liturgical monodies of medieval origin (the so-called Gregorian Chant, Old Roman Chant and Ambrosian Chant). The ‘unidimensional’ nature of the musical repertoires investigated (rhythm-free melody without accompaniment) allows the adoption of a known method based on a pseudo-distance between frequency-vectors of n-gram of consecutive symbols. Finally, we show that some specific features of musicological interest inside the three liturgical families can be naturally extracted using a statistical analysis of n-gram distributions. The results presented show that a quantitative approach is well suited to support and accompany the investigation of refined problems in musicology.